The Struggle of School Students During Tritura Period in West Sumatera - Erasiah, Erasiah; Desmaniar, Desmaniar; Martias, Martias; Oktavia, Nabila; Zein, Farid Mat (History Department, Semarang State University and Historian Society of Indonesia, 2024)
This article explores the role of high school students in West Sumatra during the Tri Tuntutan Rakyat (Tritura: Three Demands of the People) movement in 1966. Utilizing a library research approach it leverages both primary and secondary sources. Primary sources include archives and photographs from the Museum Angkatan 66 in Bukittinggi, complemented by historical narratives. Secondary sources comprise relevant books and articles. The research findings highlight that during the height of Tritura, which shook Jakarta and resonated across Indonesia, West Sumatra witnessed significant activism by school-age children, organized under KAPPI (the Indonesian Youth and Students Action Union). These students received overt support from their schools and covert backing from sympathetic Indonesian National Armed Forces (TNI) members. Schools served as operational bases for KAPPI in various locales of West Sumatra. Notably, one student, Ahmad Karim, became a martyr after being shot during a protest in Bukittinggi’s Chinatown, later receiving posthumous recognition as a hero.